O-013 The individualised dosing algorithm of follitropin delta, developed in a GnRH antagonist protocol, shows to be highly effective in a long GnRH agonist protocol. (30th June 2022) - Fernandez Sanchez, M; Larsson, P; Ferrando Serrano, M; Bosch, E; García Velasco, J A; Santamaría López, E; Mannaerts, B
Abstract: Study question: Is the individualised follitropin delta regimen based on serum anti-Müllerian hormone (AMH) concentration and body weight effective and safe in a long GnRH agonist protocol? Summary answer: Per started stimulation, the live birth rate following fresh transfer was 43% and the cumulative live birth rate following fresh and frozen transfers was 58%. What is known already: Individualised follitropin delta treatment in a GnRH antagonist protocol reduces the incidence of OHSS and/or preventive interventions without compromising live birth rates. In a multinational, double-blind, randomised trial (RAINBOW, NCT03564509) exploring the efficacy and safety of choriogonadotropin beta in women undergoing ovarian stimulation in a long GnRH agonist protocol, the control group was treated with the same individualised follitropin delta regimen based on AMH (Elecsys AMH Plus Immunoassay) and body weight. Women had one stimulation cycle and were followed up to live birth following the fresh and all frozen blastocyst transfers performed within one year after start of stimulation. Study design, size, duration: Analysis of fresh and cumulative live birth rates in 104 women (30–42 years, AMH 5-35 pmol/L) down-regulated with 0.1 mg/day triptorelin and stimulated in one cycle with a fixed individualised daily dose of follitropin delta. Triggering was performed when 3 follicles ≥17 mm. Oocytes were inseminated by ICSI; blastocyst transfer was on day 5 and remaining blastocysts were cryopreserved on day 5/6 and subsequently used for frozen transfers. Participants/materials, setting, methods: Data collection included live birth and neonatal health follow-up for all transfers of fresh or frozen embryos performed within one year after the start of stimulation. The data presented are based on all women who were down-regulated and started stimulation. The cumulative live birth rate was calculated as the percentage of women starting stimulation that had at least one live born neonate. Main results and the role of chance: Of 104 women starting stimulation, 101 had triggering. Two subjects were cancelled due to poor response and one due to adverse event. Nine subjects had transfer cancellations; six due to no day 5 blastocyst available, and one each due to risk of OHSS, adverse event, and other reason. The average daily dose of follitropin delta was 11.0±1.6 and the duration of stimulation was 10.3±1.6 days. The mean number of oocytes was 12.5±6.4; the mean number of blastocysts was 5.1±3.4; and 85% had at least one good-quality blastocyst. Following mostly single blastocyst transfer (95%), the ongoing pregnancy rate (10–11 weeks after transfer) was 43% per started stimulation. There were six cases of early OHSS (5.8%) graded as mild (3) and moderate (3) and six cases with late OHSS (5.8%) graded as moderate (3) and severe (3). In total, 92% of women had at least one fresh or frozen transfer and 150 blastocyst transfers were performed (92 fresh and 58 frozen transfers). Per started stimulation, the live-birth rate following fresh transfer was 43% and the cumulative live-birth rate following fresh and all frozen transfers was 58%. There were three neonates with congenital anomalies following fresh transfer and none following frozen transfer. Limitations, reasons for caution: This is the first clinical trial investigating the individualised follitropin delta regimen in a long GnRH agonist protocol. A final evaluation of this regimen requires comparative data. Accordingly, a randomised trial comparing follitropin delta in a long GnRH agonist protocol vs. in a GnRH antagonist protocol is currently ongoing (NCT03809429). Wider implications of the findings: The use of individualised follitropin delta dosing based on AMH and body weight in a long GnRH agonist protocol resulted in high fresh and cumulative live birth rates, and with an incidence of OHSS similar to previously reported for other FSH products in long GnRH agonist protocols. Trial registration number: NCT03564509